2017
DOI: 10.1016/j.actatropica.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing passive surveillance for T. b. rhodesiense human african trypanosomiasis in Uganda

Abstract: This study illustrates the critical role of the district health system in HAT management. The increasing proportion of cases identified at a late stage in this study indicates a major gap in lower tier levels in patient referral, diagnosis and reporting that urgently needs to be addressed. Integrating HAT diagnosis into national primary healthcare programs and providing training to medical workers at all levels is central to the new 2030 WHO HAT elimination goal. Given the zoonotic nature of rHAT, joined up ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…These include the specific disability weights given, accounting for undetected cases and the exclusion of long-term impacts on growth and neurological impairment, either by infection or drug toxicity. While over 175,000 cases of HAT were reported between 2000 and 2009 [ 11 ], the disease is found largely in remote rural areas with limited diagnostic capacity and poor access to health facilities [ 12 , 13 ]. According to the World Health Organization (WHO), in 2009 about half of cases were thought to be unreported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the specific disability weights given, accounting for undetected cases and the exclusion of long-term impacts on growth and neurological impairment, either by infection or drug toxicity. While over 175,000 cases of HAT were reported between 2000 and 2009 [ 11 ], the disease is found largely in remote rural areas with limited diagnostic capacity and poor access to health facilities [ 12 , 13 ]. According to the World Health Organization (WHO), in 2009 about half of cases were thought to be unreported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the DRC, total treatment costs for gHAT were equivalent to five months of a household’s income, rising to as much as 17 months in cases of disease complications [ 18 ]. Health seeking behaviour studies have shown that HAT patients visit numerous public and private health providers over several months before being correctly diagnosed and treated [ 13 , 19 , 20 ]. Recovery periods typically take many months and HAT is thought to lead to many long-term disabilities caused by drug toxicity and infection, although the associated morbidity has not been quantified [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of formal training for front-line medical workers, local stigma surrounding diagnosis of sleeping sickness and a delay in patients contacting medical services only exacerbates the problem of surveillance and monitoring of this disease (Mpanya et al 2012;Acup et al 2016). When an infected kissing bug takes a blood meal, T. cruzi is passed out in the insect's feces and is typically deposited near the bite wound.…”
Section: Timeline Of Trypanosome Detectionmentioning
confidence: 99%
“…Drug development, successful public health initiatives and active case-monitoring programs have all contributed to the anticipated eradication of gambiense HAT as a major public health problem in the coming decade [10]. However, vigilance and understanding of drug mechanisms and possible resistance pathways remain essential to maintain this situation, and rhodesiense HAT cannot be eliminated in this way as it is highly zoonotic [11]. Genome-wide RNAi screens identified a number of genes associated with pentamidine sensitivity that, together with evidence from melarsoprol-pentamidine cross-resistance (MPXR), identified aquaglyceroporin 2 as the primary determinant for drug-uptake [12,13], alongside lesser roles for the TbAT1/P2 aminopurine transporter and the Low Affinity Pentamidine transporter LAPT1 [14].…”
Section: Introductionmentioning
confidence: 99%